Odpowiedzi

2010-01-17T19:22:30+01:00
-3 1/4
-13 2/3
-8,2
-12,4
13 1/4
3 4/15
12 2 12
2010-01-17T19:23:07+01:00
(-5)-(-1 3/4 )= -5 + 1 3/4 = - 3 1/4

-(-1 1/3)+(-15)= 1 1/3 + -15 = -13 2/3

(-3 2/5 ) - 4,8= -3,4 - 4,8 = -8,2

(-2,2 )+(-10 1/5 )= -2,2 + (-10,2) = -12,4

-(-9) - (-4 1/4 )= 9 + 4 1/4 = 13 1/4

2 1/3 + (-5 3/5 )= 2 5/15 + (- 5 9/15) = - 3 4/15
13 3 13
Najlepsza Odpowiedź!
2010-01-17T19:32:08+01:00
(-5)-(-1 3/4) =
= (-5) + (7/4) =
= - 3 1/4

-(-1 1/3)+(-15) =
= 1 1/3 - 15 =
= 4/3 - 15 =
= -13,6

(-3 2/5 ) - 4,8 =
= -17/5 - 4,8 =
= -8,2

(-2,2 )+(-10 1/5 ) =
= -2,2 - 51 =
= -53,2

-(-9) - (-4 1/4 ) =
= 9 + 17/4 =
= 13.25

2 1/3 + (-5 3/5 ) =
= 7/3 - 28/5 =
= -3.26


22 3 22